Cold storage : a novel - Koepp, David (Ecco, an imprint of HarperCollinsPublishers, 2019)
When Pentagon bioterror operative Roberto Diaz was sent to investigate a suspected biochemical attack, he found something far worse: a highly mutative organism capable of extinction-level destruction. He contained it and buried it in cold storage deep beneath a little-used military repository. Now, after decades of festering in a forgotten sub-basement, the specimen has found its way out and is on a lethal feeding frenzy. Only Diaz knows how to stop it. He races across the country to help two unwitting security guards<U+2014>one an ex-con, the other a single mother. Over one harrowing night, the unlikely trio must figure out how to quarantine this horror again. All they have is luck, fearlessness, and a mordant sense of humor. Will that be enough to save all of humanity?